Using the Dictionary for Improving Adolescents’ Reading Comprehension of Short Scientific Texts - Becerra Cortés Ximena (Profile: Issues in Teachers' Professional Development)
<span style="font-size: 10.0pt; mso-bidi-font-size: 11.0pt; font-family: ";Verdana";,";sans-serif";; mso-fareast-font-family: ";Times New Roman";; mso-fareast-theme-font: minor-fareast; mso-bidi-font-family: ";Times New Roman";; letter-spacing: -.05pt; mso-ansi-language: EN-US; mso-fareast-language: ES-CO; mso-bidi-language: AR-SA;" lang="EN-US">This paper reports on an innovative and action research project which focused on the use of the dictionary and the prior knowledge of Colombian high school students to improve their reading comprehension of short scientific texts. Data collection instruments included students’ work gathered during two workshops, field notes, and a questionnaire. Findings showed that searching in the dictionary and activating prior knowledge seem to facilitate the use of the text to answer reading comprehension questions. Students experienced less difficulty answering questions that required literal information than those that required establishing relationships among elements of the text. They equally valued the prior knowledge of the subject and the use of the dictionary in the resolution of science workshops in English. <span style="font-size: 10.0pt; mso-bidi-font-size: 11.0pt; font-family: ";Verdana";,";sans-serif";; mso-fareast-font-family: ";Times New Roman";; mso-fareast-theme-font: minor-fareast; mso-bidi-font-family: ";Times New Roman";; letter-spacing: -.05pt; mso-ansi-language: EN-US; mso-fareast-language: ES-CO; mso-bidi-language: AR-SA;" lang="EN-US">En este artículo se reporta un proyecto de innovación y de investigación acción centrado en el uso del diccionario y el conocimiento previo adquirido de estudiantes colombianos de secundaria para mejorar la comprensión lectora de textos científicos cortos. Los instrumentos de recolección de datos incluyen el trabajo realizado por los estudiantes durante dos talleres, notas de campo y un cuestionario. Los resultados mostraron que la consulta del diccionario y la activación de conocimientos previos parecen facilitar el uso del texto para responder preguntas de comprensión de lectura. Los estudiantes encontraron menor dificultad en la resolución de preguntas que requerían información literal que en aquellas que implicaban el establecimiento de relaciones entre los elementos del texto. Ellos valoran por igual el conocimiento previo y el uso del diccionario en la resolución de talleres de Ciencias en inglés.